Analisis Pemilihan Supplier Bahan Baku Produksi Pada Industri Kecil Mebel Kayu Dengan Menggunakan Metode Fuzzy Technique For Order Preference By Similarity To Ideal Solution (Topsis) Pada Mebel Kayu Amanah Di Kecamatan Natar - Durotun Nasikah; Jati Imantoro; Salsabila Khairi (Universitas Muhammadiyah Metro, 2025)
Amanah Wood Furniture is a small and medium enterprise operating in the furniture industry using wood as the main material in making furniture, which prioritizes aesthetics in the results. There are several suppliers who provide the company's raw material needs. The previous supplier selection process was simple and manual, so it was less efficient and the results were not optimal. The method that can be used for supplier selection is the Fuzzy TOPSIS (Technique For Order Preference By Similarity To Ideal Solution) method. The problems that occur in Amanah Wooden Furniture are: (1) How to select suppliers according to the required criteria based on decision making preferences using the Fuzzy TOPSIS method in the Amanah Furniture business? (2) Using the Fuzzy Topsis method, who is the best supplier who can work together according to the company's conditions and capabilities? The sample used in this research used a purposive sampling technique because the Fuzzy YOPSIS method requires decision makers who are experts in analyzing raw material suppliers. To solve the problem, this research uses the Fuzzy TOPSIS method which is a combination of fuzzy concepts with the topsis method which is designed to pay more attention to the level of uncertainty and ambiguity that arises, as well as a weighting technique to weight the criteria objectively. Based on the research results, it shows that the decision support system uses the results of the Fuzzy TOPSIS method considering the criteria, the weight of each criterion, as well as the decision maker's assessment of suppliers based on the criteria considered to give suppliers top priority from the available alternatives